DETERMINANTS OF JOB SATISFACTION AMONG EMPLOYEES AT PRIVATE HIGHER LEARNING INSTITUTION IN PERLIS: A CONCEPTUAL PAPER - Siti Farhana Hasanudin; Noor Saidatul Natrah Saaidun; Nainatul Farzuha Nor; Nik Azlina Nik Abdullah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This is a conceptual paper for a future study based on the review of the literature related to job satisfaction and the effect of Islamic leadership behaviour, workload and co-workers’ relationship on job satisfaction in private higher learning institutions. Job satisfaction remains among the most studied industrial and organisational psychology constructs for two main reasons. First, job satisfaction is effective in addressing employees’ absenteeism, fluctuation in production, and organizational inefficiencies, such as counter-productive behaviour and sabotage and second, job satisfaction is relevant to employees’ motivation to work and to those interested in evaluating such working conditions as task diversity, work requirements, and communications. To address these issues, this study aims to investigate the factors influencing job satisfaction; Islamic leadership behaviour, workload and co-workers’ relationship guided by the Social Exchange theory. The paper went on to analyse the issues, concepts and objectives for the forthcoming study through several literatures of various disciplines. The conceptual paper signifies to supplement literatures for academics as reference for their research. The result of this future research may provide information to the management of higher learning institutions on the factors and the preventive measures that should be taken to reduce the employees’ problems and enhancing the employees’ performance towards achieving the organizational objectives and sustainability.